Teknologi Pemupukan Sistem Otomatis Menggunakan Microcontroller By Timer - M. Fahmi Assadad, Rina Dian Rahmawati, Qumaruzzaman, Vina Mufarrokhah, Dandi Kurniawan, (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The Farmer Group Association is a collection of several farmer groups who join and work together to increase economies of scale and business efficiency for sustainable agriculture. Automatic plant sprayer by timer which is arranged and designed to realize a timer-based automatic plant sprayer with a time lag that can be determined at any time. This tool is expected so that users no longer need to spend too much money and fertilize plants no longer manually. This automatic plant sprayer by timer can be used for a variety of narrow land plants and field cultivation. In this service, you can use the Service Learning (SL) method. The results obtained from this service are that the response of the Pulogedang village community is very good, satisfying and open to the development of the automatic plant sprayer, which can be seen from the results of the response questionnaire that strongly agrees with the automatic plant sprayer by the timer.